MULTICULTURAL VALUES IN INDONESIAN NOVELS OF THE 2000s - Sayuti, Suminto A; Wiyatmi, wiyatmi (LITERA, 2017)
Abstract This study was aimed at describing multicultural values, ways of expressing multicultural values, and the dynamics of multicultural values in Indonesian novels of the 2000s. The study purposively selected a sample of six novels that intensely carried the theme of multiculturalism. These were Laskar Pelangi, Larung, Jendela-jendela, Ayat-ayat Cinta, Jepun Negerinya Hiroko, and Partikel. The study used the descriptive qualitative method. The study obtained the following findings. First, there were four main multicultural values: (a) apreciasion of cultural pluralism, (b) valuing of the principles of humanism and fundamental human rights (FHR), (c) responsibility of the international society, (d) responsibility of the planet earth. Second, multicultural values are expressed through narrative elements and become an integral part of the entire story. Third, multicultural values move in the dynamics of locality to nationality and nationality to globality. Indonesian novels of the 2000s express Indonesian people in the contexts of world nation and citizens who are multicultural, having appreciative minds towards cultural pluralism, upholding humanism and FHR, taking responsibilities of sustaining the entirety of the world and planet earth. Keywords: multicultural, Indonesian novel, nasionality, globality, plurality